2021
DOI: 10.1108/jhom-04-2021-0159
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospital accreditation in selected Middle East countries: a scoping review

Abstract: PurposeThere is conflicting evidence concerning the impact of hospital accreditation programmes, including across the Middle East Region, where such programmes have been most recently implemented in Iran, Jordan and Saudi Arabia. This paper maps available evidence regarding the impact of hospital accreditation in these three countries and draws attention to knowledge gaps for consideration.Design/methodology/approachThis scoping review was conducted in 2020, using the Arksey and O'Malley framework. Five resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The KSA was an early adopter of health accreditation programmes in the Middle East region, 9 in order to improve the levels of service quality and provide a safer work environment. 10 The KSA government also launched a local accreditation programme, the Central Board for Accreditation of Healthcare Institutions (CBAHI) (see Section 2.6 ), which was mandated to grant the CBAHI accreditation to healthcare facilities, including primary health care centres (PHCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KSA was an early adopter of health accreditation programmes in the Middle East region, 9 in order to improve the levels of service quality and provide a safer work environment. 10 The KSA government also launched a local accreditation programme, the Central Board for Accreditation of Healthcare Institutions (CBAHI) (see Section 2.6 ), which was mandated to grant the CBAHI accreditation to healthcare facilities, including primary health care centres (PHCs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the KSA is considered to be in the early stages of adopting accreditation. 9 Therefore, there are significant challenges that hinder the successful implementation of these programmes. 11…”
Section: Introductionmentioning
confidence: 99%
“…An evidence-gap map of primary healthcare policy and governance in LMICs identified gaps in social accountability, public–private partnerships (PPP) and intersectoral collaboration 24. Other reviews have analysed the impacts of specific governance interventions such as demand-side and supply-side health financing strategies,25–34 stakeholder and community engagement,35 36 social accountability mechanisms,37–39 private sector partnerships40–46 and regulatory approaches 43 47–49. However, a broader mapping of the various governance interventions linked to the quality of healthcare services in LMICs is absent.…”
Section: Introductionmentioning
confidence: 99%
“…Brubakk, et al 51 conducted a systematic review that indicated that accreditation is expanding globally; however, due to insufficient evidence, no definitive conclusions could be drawn regarding its effectiveness. A scoping study by 52 indicated that accreditation programs generally improve multiple dimensions of hospital performance in the Middle East. However, some variations were noted across different countries and categories of impact.…”
Section: Introductionmentioning
confidence: 99%